Optimalisasi Peran Pemerintah Daerah dalam Mendukung Penyaluran Kredit Usaha Rakyat di Jawa Timur - Eko Aristanto (Jurnal Manajemen dan Kewirausahaan, 2019)
This study aims to analyze : 1) the relationship between fiscal capacity and APBD expenditure on Koperasi and MSME affairs; 2) the effect of APBD expenditure for Koperasi and MSME affairs and  KUR facilitator toward socialization and mentoring; and 3) the effect of socialization and mentoring on the amount of KUR debtors. The design of the study uses mixed methods, researchers combine surveys (quantitative) with case studies (qualitative). The study population was the district/city implementing the KUR program with sample selection using a purposive sampling technique. Data analysis in this research uses Chi-Square tests and Path Analysis. The research shows : 1) fiscal capacity is not related to APBD expenditure for Koperasi and MSME affairs; 2) APBD expenditure for koperasi and MSME affairs and the KUR facilitator have no significant effect on KUR socialization and assistance; and 3) socialization and mentoring have a significant effect on the number of KUR Debtors.https://doi.org/10.26905/jmdk.v7i1.2841